Small-Scale Filtration Systems: A Solution for Clean Water in Martapura River Communities: Meningkatkan Kualitas Air dan Kesehatan Masyarakat dengan Filtrasi Skala Rumah Tangga di Sungai Martapura - Zubaidah, Tien; Hamzani, Suliaman; Juanda, Juanda (Universitas Lancang Kuning, 2024)
This study examines if a small-scale filtering system can improve water quality for Martapura River residents. Over six months, the filtering system affected key water quality indicators. Turbidity dropped 85%, TDS dropped significantly, and lead and cadmium were eliminated. Around 96% of households had drinking water pH values within the recommended range. The community embraced the filtration devices, with an average daily usage rate of 87%. Waterborne infections like diarrhea, typhoid, and hepatitis A decreased, improving health outcomes. The current results are good, however future versions should focus on TDS reduction and sustainability. This study shows how simple filtration devices can enhance water quality and public health, supporting the UN Sustainable Development Goals.